2014
DOI: 10.1039/c3gc41320a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and electrochemical characterization of heteropoly acids for their optimized application in selective biomass oxidation to formic acid

Abstract: Different Keggin-type polyoxometalates have been synthesized and characterized in order to identify optimized homogeneous catalysts for the selective oxidation of biomass to formic acid (FA) using oxygen as an oxidant and p-toluenesulfonic acid as an additive. Applying the optimized polyoxometalate catalyst system H 8 [PV 5 Mo 7 O 40 ] (HPA-5), a total FA-yield (with respect to carbon in the biogenic feedstock) of 60% for glucose within 8 h reaction time and 28% for cellulose within 24 h reaction time could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
199
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 133 publications
(212 citation statements)
references
References 74 publications
12
199
0
1
Order By: Relevance
“…It has been shown that H 5 PV 2 Mo 10 O 40 can convert carbohydrates such as hemicellulose in water under rather high O 2 pressures (30 bar) to formic acid in only a 50% yield with co-formation of 50% CO 2 but cellulose reacted in only low yields 20,21 . Vanadium oxide and sodium vanadate gave similar results 22,23 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that H 5 PV 2 Mo 10 O 40 can convert carbohydrates such as hemicellulose in water under rather high O 2 pressures (30 bar) to formic acid in only a 50% yield with co-formation of 50% CO 2 but cellulose reacted in only low yields 20,21 . Vanadium oxide and sodium vanadate gave similar results 22,23 .…”
Section: Resultsmentioning
confidence: 99%
“…All the reported specific advantages [20][21][22] are maintained in this biomass valorisation technology (mild reaction conditions, precious metalfree catalyst, broad range of applicable biomasses, and simple product spectrum), while two of the main obstacles for this technology, insufficiently low FA yields and problematic FA isolation, are elegantly solved. Obviously, the long reaction times observed with the biphasic reaction system remain an important target for further optimization to improve the process economics via higher productivities.…”
Section: Discussionmentioning
confidence: 99%
“…This is in good agreement with previous studies showing that already at 20 bar O 2 pressure, the HPA catalyst re-oxidation is fast as compared to glucose oxidation. 20 To confirm that the lower FA yield in the monophasic reaction system is not due to consecutive FA decomposition under the applied reaction conditions, FA was added to an aqueous HPA-5 solution and stirred at 20 bar O 2 for 48 h. NMR data confirmed the stability of FA under the applied conditions (Fig. S15, ESI †).…”
Section: In-situ Extraction Of Reaction Mixtures From Glucose Oxidationmentioning
confidence: 96%
See 2 more Smart Citations